SAT0006 P2x7 receptor in systemic lupus erythematosus (SLE). exploring a novel pathogenetic pathway in lupus related serositis. (12th June 2018) - Furini, F.; Bortoluzzi, A.; Giuliani, A.L.; Di Virgilio, F.; Govoni, M.
Abstract : Background: Recent studies have focused attention on the involvement of innate immunity and in particular on the activation of NLRP3 inflammasome by purinergic signalling mediated by P2 × 7 receptor (P2 × 7R), in SLE pathogenesis. 1 Serositis are typical SLE manifestations often associated with increased inflammatory indices and promptly responding to colchicine whose action could be mediated by its effect on microtubules during P2 × 7R assembly. Objectives: To explore the role of innate immune system in SLE evaluating expression and activity of P2 × 7R and NLRP3, comparing patients with positive and negative history of serositis with healthy control subjects (HC). Methods: We studied SLE patients with (LS) or without (LN) history of serosites and HC matched for sex and age. Demographic, clinical, therapeutic and clinimetric data were retrospectively collected. After isolation of peripheral blood mononuclear cells (PBMCs) from whole blood by centrifugation on Ficoll gradient, P2 × 7R and NLP3 expression were evaluated by RT-PCR analysis while activity was analysed after stimulation with BzATP (P2 × 7R agonist), by measuring intracellular calcium changes using Fura2-AM fluorescent probe. Finally i n vitro IL-1β and IL6 production by short term cultured PBMCs (in RPMI and after stimulation with either LPS or BzATP or BzATP +LPS), and IL-1β and IL6 plasma levels were evaluated by ELISA. Results: 30 HC and 31 patients were enrolled: 13 (40, 6%) LS vs 18 (59, 4%) LN. 30 were female. No significant differences about demographic, disease activity and serological features were found between LS and LN and almost all patients were taking low dose steroids and immunomodulatory therapy (table 1). No significant difference in plasmatic levels of IL-1β and IL-6 were found between SLE and HC also considering separately the LS group. RT-PCR analysis of PBMC from SLE subjects showed reduced P2 × 7 and slightly augmented NLRP3 expression. In vitro IL-1β release was diminished in SLE patient (both LS an LN) respect to HC (expecially comparing LN vs HC) while IL-6 levels appeared to be higher in SLE patients (expecially LN) (table 2). Conclusions: P2 × 7R expression and activity appeared to be reduced in SLE compared to HC as demonstrated by evaluation of intracellular calcium changes and IL-1β levels produced by PBMC Conversely, IL-6 was released at higher levels from PBMC of patients compared to HC, thus suggesting that production of this cytokine could be mediated by another pathway (possibly TLR pathway 2 ). Other P2 × 7 dependent responses, such as pyroptosis or T and B lymphocyte functions, need to be investigated. Overall, these preliminary results suggest that P2 × 7R and inflammasome activation do not seem to be the main pathogenetic pathway in SLE patients with history of serositis. References: [1] Francesco Di Virgilio, et al. Purinergic signalling in autoimmunity: A role for the P2X7R in systemic lupus erythematosus?Biomedical journal2016;39:326–338. [2] The impact of agonists and antagonists of TLR3 and TLR9 on concentrations of IL-6, IL10 and sIL-2R in culture supernatants of peripheral blood mononuclear cells derived from patients with systemic lupus erythematosus. Agnieszka Klonowska-Szymczyk et al; Postepy Hig Med Dosw (online), 2017; 71: 867–875. Disclosure of Interest: None declared